(untitled) (Cardiovascular Journal, 2013)
Introduction: Myocardial edema contributed to cardiac dysfunction in different clinical circumstances. The precise pathophysiology of myocardial edema and therapeutic interventions that target it have remained largely unexplored. The lysophospholipid, Sphingosine-1-Phosphate (S1P) has been shown to decrease edema in the lung through modulation of pulmonary endothelial barrier function. We apply this agent to an isolated rat heart model of ischemia-reperfusion injury and examine its effects on subsequent myocardial edema formation. Methods: 18 isolated male Sprague-Dawley rat hearts were used in this experiment. 3 served as nonischemic controls, 7 served as ischemic controls and 8 served as the intervention group. A 20 minute ischemic period was applied to all groups except the non-ischemic controls. In the intervention group, the rat hearts were given a 30mL bolus of 10nM S1P prior to ischemia. After completion, heart were histologically analyzed to evaluate the extent of myocardial edema. Results: In the non-ischemic controls there was 13.65% (+/- 0.73%) extracellular area and 84.56% (+/- 0.89%) intracellular area. In the ischemic controls there was 24.50% (+/- 3.92%) extracellular area and 74.11% (+/- 3.90%) intracellular area. In the S1P treatment group, there was 21.55% (+/- 2.6%) extracellular area and 76.77% (+/- 2.70%) intracellular area. These differences did not reach statistical significance (p>0.05). Conclusion: In this experimental design we observed a non-significant trend in histologic myocardial edema in the S1P treatment group. We also observed a correlated trend in improved myocardial function in the S1P treatment group. Cardiovascular Journal Volume 6, No. 1, 2013, Page 47-51 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16115